DEKOMPOSISI NILAI TUKAR PETANI SUBSISTEN PADI SAWAH DI PROVINSI LAMPUNG - Mas Indah, Lidya Sari; Arifin, Bustanul; Ambya (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The exchange rate is one of the farmer welfare measuremets in Indonesia. The subsistence exchange rate refers to a measurement of farmer welfare in terms of gross income from rice farming relative to production costs and household consumption costs. The purposes of this study are to analyze rice farming income and the composition of the subsistence exchange rate (NTS) of rice farmers. The research was conducted in Gunung Sugih Village, Kedondong District, Pesawaran Regency from September 2024 to April 2025. The research sample consisted of 65 paddy field farmers. Farming analysis was used to analyze farming income and the subsistence exchange rate (NTS) utilized to analyze the decomposition of the NTS of paddy field farmers. The results show that rice farming income is economically profitable. Farmers with larger land areas have a higher Subsistence Exchange Rate (NTS) than small-scale farmers, both in terms of main consumption components including food and fuel, as well as other welfare components such as education, health, clothing, and other household needs. In addition, farmers with large land areas are also attend to allocate a larger proportion of their NTS to productive inputs such as seeds and fertilizers, indicating a more commercial orientation and higher investment capacity. This condition reflects the positive influence of land scale on production efficiency, income, and farmer welfare. Therefore, policies need to be focus on strengthening access to land, capital, and agricultural technology extension to improve the efficiency of smallholder farmers business , the subsistence exchange value, and welfare of rice farmers. Key words: exchange rate, farmer, income, subsistem, welfare